ANALISIS PENAWARAN DAN PERMINTAAN DAGING SAPI DI INDONESIA SEBELUM DAN SAAT KRISIS EKONOMI: SUATU ANALISIS PROYEKSI SWASEMBADA DAGING SAPI 2005 - KETUT KARIYASA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id)
This research intended to analyze the domestic beef production and demandinfluence factors and projected for the next ten years forward in relation with thegovernment program for “the meat self-sufficient on 2005”. This research used thenational time series data for 1970 to 1999 period. The econometric model(simultaneous regression) approach through the three stage least squares (3SLS)method had been implemented in order to reach the objectives of this research. Theanalysis of the research results shown that the variables with the economic effectsfor the domestic of beef production are the beef price it self, interest, population ofcows, the price cows and the price of feedstuff. The variables that have theeconomic effects on the beef domestic demand are the price of beef itself, the priceof fishes, the price of eggs, the price of the goat (sheep) meats, income per capitaand consumer needs or requests. The elasticity value shown that the beef productionjust only response to the beef price itself and the cows price variables change. Thedomestics demand of the beef just only response to the beef price itself and incomeper capita variables change. The analysis of the research results also shown that thedomestics beef production and demand on the economy crisis are 1.3 and 0.5 timeslower than before economy crisis. Beside that, the projection results shown that thebeef self-sufficient can not be reach, meanwhile on this year, the domestics beefproduction only 66.8 percent from the total demand.